Investigating indirect impacts of TCP connection on IMS network - Ali Abdulrazzaq K. (College of Education for Pure Sciences, 2021)
The IP Multimedia Subsystem (IMS) is recently expected to have the major architecture framework to be involved in the Next Generation Network. IMS works to bridge the multimedia communication among variety of applications over Internet. IMS bears its multimedia signals and stream through different means of transport protocols; TCP, UDP, and SCTP. TCP is a connection-oriented protocol that provides reliable data delivery and congestion control. To setup connection with TCP, IMS entities requires extra operations to complete, that operation process called (worker process) costs the multimedia server extra overload and delay. This paper investigates the indirect impacts of TCP connection that resulted from the Call Session Control Function (CSCF) servers when it deal with video communication. Two parameters are evaluated in experiment which are CPU usage and response time with two different scenarios. The experimental shows that outbound scenario performs better than the inbound scenario due to the extra operations required to setup new TCP connection for inbound